Mitochondrial Interactome: A Focus on Antiviral Signaling Pathways - Refolo, Giulia; Vescovo, Tiziana; Piacentini, Mauro; Fimia, Gian Maria; Ciccosanti, Fabiola (Frontiers in Cell and Developmental Biology, 2020)
In the last years, proteomics has represented a valuable approach to elucidate key aspects in the regulation of type I/III interferons and autophagy, two main processes involved in the response to viral infection, and to unveil the molecular strategies that viruses have evolved to counteract these processes. Besides its main metabolic roles, mitochondria are well recognized as pivotal organelles in controlling signaling pathways essential to restrain viral infections. In particular, a major role in antiviral defense is played by MAVS, an adaptor protein that coordinates the activation of interferon inducing pathways and autophagy at mitochondrial level. Here, we provide an overview of how mass-spectrometry-based studies of protein-protein interactions and post-translational modifications have fostered our understanding of the molecular mechanisms that control the mitochondria-mediated antiviral immunity.